2008
DOI: 10.1007/s10453-007-9082-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of electron spin resonance radical immunoassay for measurement of airborne orchard grass (Dactylis glomerata) pollen antigens

Abstract: We have developed a highly sensitive method for the measurement of airborne orchard grass (Dactylis glomerata: Dac g) pollen antigens using an electron spin resonance (ESR) radical immunoassay. In this immunoassay, the lowest detectable level of Dac g antigen in a sample is 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Grass and mugwort pollen, along with C. japonica are prevalent causes of pollinosis in some areas of Japan and other countries. We once focused on pollen antigens (allergens) and quantifying the amount of the major pollen antigen present in the air, such as Cry j 1or Dac g, which are common to this region (Takahashi et al , 2008, with the aim of gaining knowledge to ultimately aid pollinosis patients. However, these methods have not been widely adopted for practical use in terms of cost and the availability of automation.…”
Section: Resultsmentioning
confidence: 99%
“…Grass and mugwort pollen, along with C. japonica are prevalent causes of pollinosis in some areas of Japan and other countries. We once focused on pollen antigens (allergens) and quantifying the amount of the major pollen antigen present in the air, such as Cry j 1or Dac g, which are common to this region (Takahashi et al , 2008, with the aim of gaining knowledge to ultimately aid pollinosis patients. However, these methods have not been widely adopted for practical use in terms of cost and the availability of automation.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of industrial objects are systematically analyzed, ten methods for industrial measurement are summarized, and the basic principles for choosing the right industrial method are indicated [1] . Takahashi [2] etc, developed a highly sensitive method for the measurement of airborne orchard grass pollen antigens using an electron spin resonance (ESR) radical immunoassay. Moerlein [3] etc, shown the theory and implementation of a force measurement-based approach to controlling work-piece diameter in cylindrical grinding.…”
Section: Introductionmentioning
confidence: 99%